Effects of acute intoxication with uranyl nitrate on bone formation - Guglielmotti, M. B.; Ubios, Angela M.; Molinari de Rey, Beatriz L.; Cabrini, Rómulo Luis (Birkhäuser Verlag Basel, 1984)
Fil: Guglielmotti, M. B. Comisión Nacional de Energía Atómica; Argentina